The historical context and the importance of recreational activities in teaching chemistry to build knowledge (Research, Society and Development, 2020)
In recent years there has been a considerable increase in the number of publications involving the application of games for teaching Chemistry. However, such publications not necessarily exhibit adequate theoretical references, or not related to teaching and learning issues. This work analyzes a series of scientific articles from several magazines, between the years 2015-2020. They were separated into three categories: a) traditional games applied in any discipline; b) traditional games in the teaching of chemistry; c) application of virtual games in the teaching of Chemistry. Into this last category, three articles were analyzed to verify which methodologies were applied to validate the data obtained from the application of traditional games, virtual ones, or both. The results show that students accept all types of games (traditional or virtual), are capable to better understand and consolidate the content taught by the teacher. By diversifying its methodology, the teacher can awaken the student’s motivation to attend classes and study contents, making it easier to absorb it, and at the same time improve the students’ academic performance.